PENGARUH MEDIA POP UP BOX TERHADAP HASIL BELAJAR SISWA PADA MATERI MODEL ATOM - Rina Elvia; Fajri Aneksa; Hermansyah Amir (University of Bengkulu, 2026)
This study aims to determine the effect of using Pop Up Box media on students’ learning outcomes in the topic of Atomic Models in Grade X at SMA Negeri 10 Bengkulu City. The method used in this research was a quasi-experimental design involving two groups. The sample was selected using a purposive sampling technique, with class XA serving as the experimental group and class XB as the control group. The research instruments included a learning achievement test Data analysis using the Mann–Whitney test yielded a Sig. (2-tailed) value of 0.001 < 0.05, indicating a significant difference in the learning outcomes between the experimental and control classes. This also suggests that the treatment given to the experimental class had an effect on students’ learning outcomes. The results showed that classical mastery learning had not yet been achieved, with a mastery percentage of 45.2%. This condition indicates that the use of Pop Up Box media was not yet fully effective, but it had a positive influence on improving students’ learning outcomes and motivation during the learning process. Overall, the Pop Up Box media can serve as an interesting and appropriate alternative learning medium to help students understand abstract concepts in chemistry. Further development in media design and the application of more varied learning strategies are needed to optimize learning outcomes.